Changes of cholinesterase activity, histology and proteome of puntius javanicus liver upon exposure to copper - Mohd Khalizan Sabullah (2015)
The present study was carried out to investigate the effect of copper sulfate (CUSO₄) exposure on cholinesterase (ChE) activity, histology, and proteome of Punt ius javanicus liver. Acute toxicity test to obtain lethal concentration (LC) values (LC₅₀o and LC10) of CUSO₄ was initially done by exposing eight groups of fish for 96 hours with 2.0, 4.0, 6.0, 8.0, 10, 13, 15 and 20 mg/L of CUSO₄, respectively. Based on Finney method (Probit analysis) of calculation, LC₅o and LC10 of CUSO₄ were determined as at 10.30 mg/L and 6.11 mg/L, respectively. Sublethal CUSO₄ concentrations of 0, 0.1,0.3, 0.5, 1.0 and 5.0 mg/L (Lower than LC10 value i.e. with 100% fish survival) were used to treat six groups of P. javanicus fish including a control for 96 hours. The liver of each treated and control fish was subjected to cholinesterase activity test, histology, and proteomic studies. For ChE activity study, an optimal assay condition of purified ChE was determined as at the pH 7.5 and at the temperature in the range of 25 to 35°C in 0.1M Sodium Phosphate buffer. As compared to other synthetic substrate, butyrylthiocholine iodide (BTCi) was selected as ChE specific substrate with the highest maximal activity (Vmax), lowest biomolecular constant (Km) and the highest catalytic efficiency ratio at the value of 53.49 (50.12 to 56.87)µmol/min/mg, 0.23 (0.16 to 0.31) mM, and 232.57, respectively. Storage condition showed that ChE need to be preserved in refrigerated condition. Metal ion in-vitro test showed that Cu, chromium and mercury had the capability to lowering the activity of ChE more than 50%. The combination of pairwise metal ion enhanced the inhibitory effect of more than 60%. Half inhibitory effect (IC₅o) of Cu ion towards the ChE In vitro was found as at 0.0948 (0.06797 to 0.1628) mg/L. In vivo effect showed that at 0.1 mg/L of CUSO₄, the activity of ChE was increased significantly (p<0.05) by 6% compared to the control. However, the percentage activity of ChE was decreased to 95.41, 87.60, 84.60 and 73.00 % at the Cu concentration treatment of 0.3, 0.5, 1.0 and 5.0 mg/L, respectively. The toxicity effect of Cu on P. javanicus liver was visualized using light microscope and transmission electron microscope (TEM). Histology on the affected cells showed abnormalities of nucleus polygonal shape along with' parenchymal vacuolation, dilation and congestion of sinusoid. At the higher CUSO₄ exposure (0.5, 1.0 and 5.0 mg/l), hepatostructure was significantly affected as indicated by the increasing number of dilation and congestion of sinusoids, vacuolation, macrophage activities and peliosis. The damage level and HSI value were increased and in contrast the number of hepatic nuclei per mm2 were decreased as again associated with the increasing Cu treatment concentrations. Through an observation of selected hepatocyte ultrastructure (liver of treated goups with 0.5, 1.0 and 5.0 mg/l CUS04) using TEM, other abnormalities i.e. the development of pyknotic nucleus along with damaged organelles such as mitochondria, Golgi apparatus and endoplasmic reticulum disorientation were determined. Irreversible cell injury was also determined, in which hepatic nuclei had seen to undergo for karyorrhexis with the formation of apoptotic body that consisted of free scattered damaged organelles. Proteomic study based on second dimension electrophoresis (2D-PAGE) was performed whereby the patterns of resolved protein spots on the gels were visualized using calibrated densitometer G-800 after stained with a modified silver staining method. The estimated total number of protein spots of 1791 were matched and compared among the control and treated gels. Subsequently, 10 unique protein spots on the coomasie blue G-250 stained gels were selected (based on fold change more than 2.0) and subjected to identificaton by using MALDI-TOF-TOF mass spectrometry combined with data mining in SwissProt, UniProt and NCBlnr. The identity and putative function of five upregulated (Gastrotropin, VAT-1L, hemogobin-!3, two subunit of hemoglobin-a), four downregulated (Trypsin, ZC4H2, Islet-2A and hemoglobin-ß AlB) and one up and downregulated (Parvalbumin) protein spots were determined in this study as shown in their individual bracket, respectively. In conclusion, Cu is evident to significantly affects the ChE activity, histology and proteome of P.javanicus liver. This study has generated several novel fundamental knowledge of the adverse effects of Cu on a fish model, which is potentially being used in future as an alternative biomarker or biosensor for the presence of contaminant especially Cu in the environment.